Elucidating the Multi-Targeted Role of Nutraceuticals: A Complementary Therapy to Starve Neurodegenerative Diseases - Behl, Tapan (Int J Mol Sci, 2021)
The mechanisms underlying multifactorial diseases are always complex and challenging. Neurodegenerative disorders (NDs) are common around the globe, posing a critical healthcare issue and financial burden to the country. However, integrative evidence implies some common shared mechanisms and pathways in NDs, which include mitochondrial dysfunction, neuroinflammation, oxidative stress, intracellular calcium overload, protein aggregates, oxidative stress (OS), and neuronal destruction in specific regions of the brain, owing to multifaceted pathologies. The co-existence of these multiple pathways often limits the advantages of available therapies. The nutraceutical-based approach has opened the doors to target these common multifaceted pathways in a slow and more physiological manner to starve the NDs. Peer-reviewed articles were searched via MEDLINE and PubMed published to date for in-depth research and database collection. Considered to be complementary therapy with current clinical management and common drug therapy, the intake of nutraceuticals is considered safe to target multiple mechanisms of action in NDs. The current review summarizes the popular nutraceuticals showing different effects (anti-inflammatory, antioxidant, neuro-protectant, mitochondrial homeostasis, neurogenesis promotion, and autophagy regulation) on vital molecular mechanisms involved in NDs, which can be considered as complementary therapy to first-line treatment. Moreover, owing to its natural source, lower toxicity, therapeutic interventions, biocompatibility, potential nutritional effects, and presence of various anti-oxidative and neuroprotective constituents, the nutraceuticals serve as an attractive option to tackle NDs.